(untitled) (Journal of EAHIL, 2019)
We describe the journey of a British mid-20th century collection of asylum art from the objects’ creation, through decades of obscurity, to an influential place among the international collections. Key aspects include the development of a contemporary narrative and ongoing work on the ethics of viewing these collections. We describe how the Wellcome Library is working to understand and catalogue this large collection.